Determinants of body composition among peri-menopausal women of Bilaspur district, Chhattisgarh, India - Suman Sahu; Rajesh K. Gautam (BMC Public Health)
Abstract A cross-sectional study was conducted among the peri-menopausal women to find out determinants of body composition. A total of 200 peri-menopusal women were recruited (≥ 40 years) from rural and urban areas of the district Bilaspur (CG). Among the studied respondents the mean age for peri-menopausal women was 42.62 ± 3.40 years. Body fat was found very high among 58%, visceral fat was normal among 64% and skeletal muscle mass was low among 73% of the respondents. WHR was found high among 60.5%, on the basis of BMI majority of them were overweight and obese (52.5%). Age at peri-menopause was found to have significant and positive correlation with body-age (r = 0.18*), whereas it was negatively correlated with skeletal muscle mass (r = -0.14*). Regression analysis reveals that the main determinants for age at peri-menopause were body age, skeletal muscle mass, BMI and bodyweight.